Wellbeing-enhancing occupation and organizational and environmental contributors in long-term dementia care facilities: an explorative study. (January 2014) - Smit, Dieneke; Willemse, Bernadette; de Lange, Jacomine; Pot, Anne Margriet
ABSTRACT Background: Occupation remains an unmet need in long-term dementia care. To increase residents' occupation, knowledge of types of occupation related to wellbeing, and organizational and environmental characteristics encouraging involvement in these types of occupation, is indispensable. Methods: In this explorative study, Dementia Care Mapping was used to study involvement in different types of occupation and wellbeing among 57 residents of 10 dementia care facilities. For each type of occupation, mean experienced wellbeing was studied. Occupation types with high mean wellbeing scores were classified as "wellbeing-enhancing occupation." Care facilities were ranked according to the mean time residents spent in types of wellbeing-enhancing occupation. Using information on staff-to-resident ratio, individual space, and items of the Physical Environment Evaluation Component of Dementia Care Mapping, organizational and environmental characteristics of the facilities were compared to study their relationship with wellbeing-enhancing occupation. Results: Reminiscence, leisure, expression, and vocational occupation had greatest potential to enhance wellbeing, but these types were seldom offered. Much variation existed in the extent to which wellbeing-enhancing occupation was provided. Long-term care facilities that did so more frequently generally had a more homelike atmosphere, supported social interaction through the environment, and had no central activity program. Conclusions: This study suggests that it is possible to engage residents in wellbeing-enhancing occupation, within current means of budget and staff. The physical environment and care organization might play a role, but the key factor seems to equip staff with skills to integrate wellbeing-enhancing occupation into care practice.